Associations of Urbanicity and Sociodemographic Characteristics with Protective Health Behaviors and Reasons for Leaving the Home During COVID-19. (19th November 2020) - Burford, Katie; Dooley, Erin; Lanza, Kevin; Knell, Gregory
Background: Few data exist on the characteristics of U.S. adults' compliance with movement restrictions (i.e., "stay-at-home" orders) and protective health behaviors during the COVID-19 pandemic. Purpose: To evaluate the associations of individual- and area-level characteristics (urbanicity) with reasons for leaving home and subsequent protective health behaviors during the COVID-19 pandemic. Methods: A convenience sample of U.S. adults (N = 2, 441) completed a 15-minute self-report online questionnaire. Exclusion criteria included: 1) missing ZIP; 2) currently sick with COVID-19; 3) difficulty with errands; and 4) "essential service" employment. Multivariable logistic regression models estimated the odds of citing reasons for leaving home and protective health behaviors by levels of urbanicity and sociodemographic factors. Data collection and analyses were conducted between April and June 2020. Results: The analytic sample ( n = 1, 374 ) was primarily Non-Hispanic white (79%), female (72%), urban residents (43%), and college degree or higher (85%). Rural residents (versus urban residents) had lower odds of wearing a mask (OR = 0.60, 95%CI:0.43–0.83). Women (versus men) had lower odds of leaving the home for shopping (grocery: OR = 0.51, 95%CI:0.31–0.80; essential: OR = 0.68, 95%CI:0.52–0.88), and higher odds of social distancing (OR = 2.34, 95%CI:1.12–4.85) and wearing a mask (OR = 1.58, 95%CI:1.20–2.08). Older adults [(≥50 years) versus younger adults (18–34 years)], had higher odds of leaving home for grocery shopping (OR = 2.07, 95%CI:1.25–3.48) and higher odds of wearing a mask (OR = 2.02, 95%CI:1.42–2.91). Conclusions: The differences for leaving home and protective health behaviors by age, sex, and urbanicity can be useful for future health promotion strategies to encourage best practices that limit the spread of COVID-19.